Blood Donation and Misconceptions- A Nationwide Survey in Dental Hospitals of Pakistan - Hashmi Shahkamal; Tanwir Farzeen; Rai Kelash; qadeer Abdul; Baig Maham (Journal of Hematology and Oncology Research, 2017)
Background Blood donation is a common practice in many countries of the world and it benefits many of the people suffering from conditions which require blood transfusions. The blood donated should be appropriately screened for certain infectious diseases such as HIV/AIDS, Hepatitis B, Syphilis and Gonorrhea through serological tests. Materials and Methods This cross sectional study was conducted from January 2014 to August 2014, Data was collected from eight dental hospitals in four provinces of Pakistan. Attendants of the patients admitted in the surgical ward with age more than 16 years were included. Knowledge and practices of the participants were evaluated through a self-administered questionnaire. Ethical consent was obtained from the ethical committee or concerned authority of all eight hospitals. Results Response rate was 84 %. In total 55% male and 45 % female participated with 15.5% of the total sample population was under the age of 20 years. The age group with the maximum number of participant was between 20 to 39 years of age. 26% and 22.5% of the males and female participants respectively had knowledge. About blood donation, lesser percentage of attendants, 7.2% of the males and 4.6% declared that they had donated blood in the past. Based on education levels, it was highest among graduates (3.5%) and less in primary educated (2.2%) and uneducated respondents was 0.7%. 18% of the males and 17% females asserted that they hold some kind of fear of blood donation. Conclusion The population is not adequately knowledgeable regarding blood donation. There is a need for proper campaign to educate masses at national level within Pakistan to promote more people to become regular volunteers.
Keywords: Blood donation